Influence of Photoperiod, Light Intensity and Their Interaction on Growth Performance and Carcass Characteristics of Broilers Grown to Heavy Weights - Olanrewaju , H.A.; Purswell, J.L.; Collier, S.D.; Branton, S.L. (International Journal of Poultry Science, 2012)
The effects of photoperiod, light intensity and their interaction on growth performance and carcass characteristics of broilers were investigated in 2 trials. The experiment was consisted of a factorial arrangement of treatments in a randomized complete block design. In each trial, all treatment groups were provided 23L:1D with 20 lx of intensity from placement to 7 d and then subjected to the treatments. The 9 treatments consisted of 3 photoperiods [long/continuous (23L:1D) from d 8-d 56; regular/intermittent (2L:2D) and short/non-intermittent (8L:16D) from d 8-d 48 and 23L:1D from d 49-d 56, respectively] and exposure to 3 light intensities (10, 5.0 and 0.5 lx) from d 8 through d 56 at 50% RH. Birds were provided a four phase-feeding program and water was provided ad libitum. Birds and feed were weighed on 0, 14, 28, 42 and 56 d of age for growth performance evaluation. At 56 d of age, 20 (10 males and 10 females) birds from each room were randomly selected, slaughtered and processed to determine weights and yields. Broilers subjected to a short/non-intermittent photoperiod showed the significantly (P